Calamitous events? Exploring perceptions of disaster. (1st June 2023) - Coates, Robert; Warner, Jeroen
Abstract: In this introductory paper we discuss the emergence of the 'event' as a critical point of interrogation of contemporary understandings of disaster. While the practicalities of DRR are underpinned by an applied vision of disaster studies largely built around hazards scholarship, developments within a number of theoretical perspectives increasingly doubt the ability of this objectivist and 'experiential' approach to reduce risk in the longer term. Here, we categorise these various challenges as revealed through the SI's cases and theoretical interventions, and in selected wider scholarship, and assess what they mean for disaster interpretation, prediction and politicisation. We frame the eight articles making up the SI within an overarching view of the event based around social interpretations of space, place, time, and nature. (Re)assessing calamitous events, we argue, is prescient in a contemporary global predicament focussed on present and future 'climatic threats'.